Evaluation of outcomes after reoperative neck dissection due to thyroid cancer - Wierzbicka, Małgorzata; Waśniewska-Okupniak, Elżbieta; Banaszewski, Jacek; Pabiszczak, Maciej; Piorunek, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study was to assess the results of surgical treatment of cervical recurrences in patients with thyroid cancer. Material and methods : We assessed 66 reoperations of thyroid cancer recurrences in 51 patients. Reoperative surgeries covered I–VII neck levels. Results and conclusions : The localization of cervical recurrence and the number of removed nodes did not depend on the type of thyroid cancer. Metastatic spread was predominantly observed in the central neck. Bilateral changes tended to be observed more often in younger patients (p = 0.07). Radical neck dissections were performed more often at younger age (p < 0.01). Postoperative vocal cord paresis was noted in 13 patients; in 5 permanent tracheotomy was necessary, and 2 underwent laser glottis procedures (posterior cordectomies). Two patients died in the postoperative period – 1 due to chylothorax and 1 due to severe bleeding from the common carotid artery.